Direct radiocarbon dating and stable isotopes of the neandertal femur from Les Rochers-de-Villeneuve (Lussac-les-Châteaux, Vienne) - Cédric Beauval; François Lacrampe-Cuyaubère; Bruno Maureille; Erik Trinkaus (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Direct radiocarbon dating of the Neandertal femoral diaphysis from the Rochers-de-Villeneuve (Lussac-les-Châteaux, Vienne) has yielded an age of 45,200 ± 1,100 14C years B.P. (OxA-15257) [48,455 ± 1,878 cal. years B.P.], and stable isotope values of δ13C = - 19.0‰ and δ15N = 11.6‰. The direct radiocarbon date makes it the oldest directly dated European Neandertal specimen, even though others have securely associated radiocarbon dates in the same time range. The stable isotopes are similar to those for other OIS 3 European Neandertals and indicate a relatively high trophic level for this individual.